Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 9 - Cumulative Review: 24e

Answer

$-5y^{2}$

Work Step by Step

$\sqrt[3] (-125y^{6})=\sqrt[3] (-125\times y^{6})=\sqrt[3] (-125)\times\sqrt[3] (y^{6})=-5y^{2}$ We know this because $(-5)^{3}=-125$ and $(y^{2})^{3}=y^{2\times3}=y^{6}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.